2015
DOI: 10.1227/neu.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Resolution of Brain Ischemic Hypoxia After Cerebral Revascularization in Moyamoya Disease

Abstract: Direct anastomosis quickly improves cerebral oxygenation, immediately reducing the risk of ischemic stroke in both pediatric and adult patients. Intraoperative PtiO2 monitoring is a very reliable tool to verify the effectiveness of this revascularization procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
1
8
0
1
Order By: Relevance
“…It is possible that based on these findings, PbtO2/PaO2 and PbtO2/FiO2 ratio may be a better indicator to severity of brain injury than absolute PbtO2. The limitations of standalone PbtO2 monitoring was recognized by Arikan et al (35) who were able to calculate a hypoxic threshold using a ratio of PbtO2/PaO2 suggesting that in the absence of hypoxemia (low PaO2) and at a constant cerebral metabolic rate of oxygen (CMRO2), ratios <0.10 indicated covert hypoxia and a deficient delivery of oxygen into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that based on these findings, PbtO2/PaO2 and PbtO2/FiO2 ratio may be a better indicator to severity of brain injury than absolute PbtO2. The limitations of standalone PbtO2 monitoring was recognized by Arikan et al (35) who were able to calculate a hypoxic threshold using a ratio of PbtO2/PaO2 suggesting that in the absence of hypoxemia (low PaO2) and at a constant cerebral metabolic rate of oxygen (CMRO2), ratios <0.10 indicated covert hypoxia and a deficient delivery of oxygen into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, they carry the risk of postoperative hyperperfusion that could lead to neurological deficits. [2][3][4] We reported previously that hyperperfusion-related transient neurological deficits (TNDs) occurred in 31.5% of adult patients who underwent direct bypass procedures.…”
mentioning
confidence: 99%
“…Previous studies reported that STA-MCA bypass increases STA and MCA blood flow during the early vascular remodeling period (14,15). The increase of STA blood flow may be associated with the low resistance of the intracranial vascular bed, while the increase of MCA blood flow may be due to the support of the STA.…”
Section: Discussionmentioning
confidence: 94%
“…Intracranial and extracranial vascular reconstruction surgery mainly includes direct and indirect revascularization. Direct revascularization increases the cerebral blood flow and instantly improves cerebral metabolism (14,15), but the drawback is that STA or MCA branches of moyamoya patients may be fragile and easily occluded; thus, the long-term effect of direct revascularization remains elusive. In addition, patients with direct revascularization are prone to developing cerebral hemodynamic disturbances and perioperative complications (16).…”
Section: Discussionmentioning
confidence: 99%